FORMATION OF EDUCATIONAL - ETHOLOGICAL AND MORAL VALUES IN PRIMARY SCHOOL STUDENTS (World Bulletin of Social Sciences, 2024)
In the Republic of Uzbekistan, the education reform is aimed at improving the morale of individual personnel, improving modern teaching and upbringing methods. As a point of view, both the class and the moral and ethical qualities educate the staff to solve the problem described in the article is the movement for help.
Keywords: Ethical education; skills development-compliance with ethical standards; formation of ethical personnel